2016
DOI: 10.1515/afmnai-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Fetuin-A and Procalcitonin in the Diagnosis of Infection in Patients with Febrile Seizure

Abstract: Fetuin-A level decreased and PCT level increased in FS patients in comparison to those in the control group. These changes are significantly increased (p<0.05) in the positive CRP group compared with that of the negative CRP group. Kernel density estimation showed that procalcitonin is a better indicator of the infection in FS children than fetuin-A . Procalcitonin is more sensitive and specific than fetuin-A and when used together they produce 100% sensitivity and specificity for the diagnosis of bacterial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…A similar result was obtained by Salam OA, who observed significantly higher serum levels of CRP, IL-6 and Total WBC count in febrile patients in relation to negative control children and in FS children in comparison to FC children [24] . Al-Hakeim HK et al shown increase CRP and PCT in FS children in comparison with a healthy control group [25] . Interestingly, serum PCT levels were increased significantly in FS as compared to the healthy control group while no statistical difference between FS and FC.…”
Section: Discussionmentioning
confidence: 97%
“…A similar result was obtained by Salam OA, who observed significantly higher serum levels of CRP, IL-6 and Total WBC count in febrile patients in relation to negative control children and in FS children in comparison to FC children [24] . Al-Hakeim HK et al shown increase CRP and PCT in FS children in comparison with a healthy control group [25] . Interestingly, serum PCT levels were increased significantly in FS as compared to the healthy control group while no statistical difference between FS and FC.…”
Section: Discussionmentioning
confidence: 97%